Evaluation of factors responsible for lactation failure-hospital based study - Sreekantham, Sravya Sree; Pratima, Piduru; Ramisetty, Uma Mahesh; Belavadi, Gangadhar (International Journal of Contemporary Pediatrics, 2019)
Background: Exclusive breastfeeding is an essential part of early infant feeding. Promotion of EBF is the most effective way to reduce the infant mortality rate. This study was carried out to identify factors affecting EBF among mothers attending Narayana medical college hospital Nellore. Aim and objectives of the study was to know the incidence of lactation failure and to evaluate the factors responsible for lactation failure. Methods: Hospital-based cross-sectional study conducted from July 2018 to September 2018 involving a total of 100 mothers with the help of a proforma containing predesigned questionnaire. Demographic data of mother, obstetric details, mode of delivery, birth weight, details of antenatal advice about breastfeeding and practices, pre-lacteal feeds, current feeding practice, problems encountered during breastfeeding, anatomical problems were noted. The data collected were tabulated and statistically analyzed. Results: At the end of the study, among 100 mothers, 24 mothers are reported to have lactation failure and feeding babies with formula feeds. Among the variables taken into consideration pre-lacteal feeds, problems encountered during breastfeeding, breast diseases showed a statistically significant association with lactation failure. Mean weight gain in breastfeeding mothers and mothers with lactation failure is 11.3 kgs and 10.04 kgs respectively. Mean hemoglobin in breastfeeding mothers and mothers with lactation failure is 10.43 g/dl and 9.91 g/dl respectively. Conclusions: The results provide information about the relation between breastfeeding failure and its association with factors that contribute to it.